PERANCANGAN PROGRAM MANAJEMEN DATA BERBASIS WEBSITE PADA POSYANDU ANGGREK IV - Yulianto, Hendra Dwi; Lase, Mareanus; Basri, Hasan; Alfarizi, Salman; Gunawan, Deni (Journal of Information System, Informatics and Computing, 2025)
Manual data recording still practiced at Posyandu Anggrek IV RW 09 Bintara Jaya Bekasi often causes several issues, including input errors, delays in accessing information, and frequent data loss. These problems directly impact the accuracy of child growth monitoring and reduce the overall efficiency of posyandu services. In response to these challenges, this research developed a web-based data management system designed to help posyandu kader manage child data, weight and height records, immunization schedules, and activity reports digitally. The system aims to streamline workflow, improve data accuracy, and provide real-time access to information. Development followed the Waterfall model and applied the linear search algorithm as a simple yet effective solution for data retrieval. The technologies used include HTML, CSS, JavaScript, PHP, MySQL, and the CodeIgniter framework. Implementation results show that the system successfully simplifies the tasks of posyandu kader, reduces input errors, and contributes positively to the effectiveness of health services. As a result, Posyandu Anggrek IV is now able to deliver services in a more modern, accurate, and efficient manner.